Like wildfire : the rhetoric of the civil rights sit-ins - O'Rourke, Sean Patrick; Pace, Lesli K. (Studies in rhetoric/communication., 2020)
"The sit-ins of the American civil rights movement were extraordinary acts of dissent in an age marked by protest. By sitting in at "whites only" lunch counters, libraries, swimming pools, and churches, young African Americans and their allies put their lives on the line, fully aware that their actions would almost inevitably incite hateful, violent responses from entrenched and increasingly desperate white segregationists. The simplicity of the act, coupled with the dignity and grace exhibited by participants, lent to the sit-in movement's sanctity and peaceful power. These cohesive essays from leading scholars offer a new appraisal of the origins, growth, and legacy of the sit-ins, largely ignored in scholarly literature. By focusing on the persuasive power of demanding space, the contributors articulate the ways in which the protestors' battle for basic civil rights shaped social practices, laws, and the national dialogue"--